Nurse plants transfer more nitrogen to distantly related species. Issue 5 (19th April 2017) - Montesinos‐Navarro, Alicia; Verdú, Miguel; Querejeta, José Ignacio; Valiente‐Banuet, Alfonso
Abstract: Plant facilitative interactions enhance co‐occurrence between distant relatives, partly due to limited overlap in resource requirements. We propose a different mechanism for the coexistence of distant relatives based on positive interactions of nutrient sharing. Nutrients move between plants following source–sink gradients driven by plant traits that allow these gradients to establish. Specifically, nitrogen (N) concentration gradients can arise from variation in leaf N content across plants species. As many ecologically relevant traits, we hypothesize that leaf N content is phylogenetically conserved and can result in N gradients promoting N transfer among distant relatives. In a Mexican desert community governed by facilitation, we labelled nurse plants ( Mimosa luisana ) with 15 N and measured its transfer to 14 other species in the community, spanning the range of phylogenetic distances to the nurse plant. Nurses established steeper N source–sink gradients with distant relatives, increasing 15 N transfer toward these species. Nutrient sharing may provide long‐term benefits to facilitated plants and may be an overlooked mechanism maintaining coexistence and increasing the phylogenetic diversity of plant communities.